Epidemiologic investigation of the efficiency of bronchial asthma preventive pharmacotherapy (ETAC) - O. S. Fyodorova; Yu. A. Petrovskaya; M. M. Fedotova (Бюллетень сибирской медицины, 2004)
During the last decade numerous investigations on the study of different guidelines efficiency in primary prophylaxis of bronchial asthma (BA) has been fulfilled. In the present article a publication review devoted to the analysis of the greatest population investigation (ETAC – Early Treatment of the Atopic Child) results has been presented.